Drosophila melanogaster homolog of Down syndrome critical region 1 is critical for mitochondrial function. - Chang, K.T.; Min, K.T. (Nature Neuroscience, 2005)
Mitochondrial dysfunction has emerged as a common theme that underlies numerous neurological disorders, including Down syndrome. Down syndrome cultures and tissues show mitochondrial damage such as impaired mitochondrial enzyme activities, defective mitochondrial DNA repairs and accumulation of toxic free radicals, but the cause of mitochondrial dysfunction remains elusive. Here we demonstrate that the Drosophila melanogaster homolog of human Down syndrome critical region gene 1 (DSCR1), nebula (also known as sarah, sra), has a crucial role in the maintenance of mitochondrial function and integrity. We report that nebula protein is located in the mitochondria. An alteration in the abundance of nebula affects mitochondrial enzyme activities, mitochondrial DNA content, and the number and size of mitochondria. Furthermore, nebula interacts with the ADP/ATP translocator and influences its activity. These results identify nebula/DSCR1 as a regulator of mitochondrial function and integrity and further suggest that an increased level of DSCR1 may contribute to the mitochondrial dysfunction seen in Down syndrome.